Religious Exemptions in Ancient China - Brady Earley (Australian Journal of Law & Religion)
The issue of religious exemptions is a major feature in contemporary debates over religious freedom and equality rights. This article presents evidence of Confucianist religious exemptions in law dating back to 200 BCE in ancient China. Even with this large disparity in time, there are some surprising parallels between ancient and contemporary religious exemptions in law and the debates that have accompanied them. The article argues that religious exemptions — whether modern or ancient — run to the relationship between rights and responsibilities. It suggests modern approaches towards religious exemptions may profit from greater attention to concepts like human dignity that do not allow duties to be overshadowed by rights.